Additively manufactured fine-grained Al–Fe–Cu-Sc-Zr alloy with resistance to brittleness under high temperature - Qianyu Shi; Jibing Chen; Junsheng Chen; Yueting Wang; Xizhen Xia; Ruidi Li (Journal of Materials Research and Technology)
Existing additively manufactured aluminum alloys exhibit a sharp decrease in yield strength at moderate temperatures (200°C-400 °C), failing to meet the high-temperature resistance required in the complex service environments of aerospace applications. In this paper, an Al-2.5Fe–2Cu-0.6Sc-0.3Zr alloy material was designed and formed by laser powder bed fusion (L-PBF) technology. The optimal composition ratio was obtained by comparing the formed structures and properties, and then the phase composition, microstructure, precipitation distribution and mechanical properties were characterized and analyzed at high temperature. The result shows that the alloy's primary precipitate phases are Al6Fe (Al23CuFe4) and L12-Al3(Sc, Zr) at nano scale. Adding Zr and Sc, the thermal stability of Al6Fe is enhanced, delaying its transformation to the θ-Al13Fe4 phase and refining the particle size. The Al23CuFe4 phase, stabilized thermodynamically by substituting of Cu for Al atoms in the orthorhombic structure (oC28), also contributes to the stabilization of the Al6Fe phase. Moreover, This aluminum alloy obtained a yield strength of 449 MPa at room temperature and a yield strength of 142 MPa at 300 °C. In addition, it also shows excellent brittleness resistance under high temperature, which is better than most L-PBF aluminum alloys reported so far. These findings offer valuable insights for the future development of aluminum-based alloys with heat-resistant performance, and promising strategies for addressing particle coarsening under high temperature and intermediate-temperature brittleness.